Teratogenicity test of individual and combined toxic effects of tebuconazole fungicide and lead-acetate on chicken embryos - Szemerédy, Géza; Kormos, Éva; Somody, Gergő; Buda, István; Szabó, Rita; Lehel, József; Budai, Péter (Acta Agraria Kaposváriensis, 2018)
The aim of this study was to determine the individual and combined toxic effects of MYSTIC 250 EC fungicide (tebuconazole 250 g/l) and lead acetate on the development of chicken embryos. The chicken eggs were dipped in the solution or emulsion of the test materials for 30 minutes on the first day of incubation (day 0). The applied concentrations of lead acetate were 0.01% and of fungicide MYSTIC 250 EC was 0.1% corresponding to plant protection practice. The chicken embryos were examined on day 19 by the followings: rate of embryo mortality, body weight, type of developmental anomalies by macroscopic examination. The body weight was evaluated statistically by the one-way ANOVA with Tukey Dunnett post-test, the embryo mortality and the developmental anomalies were analyzed by Fisher test. Our teratogenicity study revealed that the combined administration of lead acetate and tebuconazole containing fungicide formulation (MYSTIC 250 EC) caused a significant reduction in body weight of embryos and increased the rate of embryonic mortality in both of applied group. The joint toxic effect of lead acetate and MYSTIC 250 EC is an additive effect compared to the individual toxicity of the test materials.